Chicken manure, chemical fertilizer and their combination affect yield and post-harvest shelf-life of carrot (Daucus carota L.) - Maxime Merlin Tonfack Djoufack; Eric Bertrand Kouam; Mariette Anoumaa; Edith Marius Kouam Foko; Gilles Raoul Lontsi Meli; Pierre Marie Kaktcham; François Ngoufack Zambou (Academia Biology, 2025)
Inadequate cultivation practices of carrots often result in lower yields. Proper soil fertilization combined with a good choice of variety can contribute to both qualitative and quantitative optimization of carrot production. Although several works have been carried out on carrots, there is still a lack of information regarding the influence of the types and doses of fertilizers applied in the field by farmers in Cameroon on yield and post-harvest shelf-life of the most frequently grown carrot varieties. This study aimed to determine the interactions between carrot variety and fertilization on the yield attributes and post-harvest conservation of carrots. Nine treatments involving individual and combined applications of chemical fertilizer (NPK: 20-10-10) and chicken manure were tested on five carrot varieties (New Kuroda, Pamela+, Madona, Amazonia, and Vanessa F1) in a split-split plot design with three replications. Yield variables were measured after 110 days of experimentation, followed by measurement of post-harvest shelf-life for thirty days. The best yield was obtained with 10 t ha−1 chicken manure. The variety Pamela+ was the most productive. This fertilizer/variety combination was identified as the best interaction for achieving optimal performance. The maximum storage time observed was 20 days. Application of chicken manure at 5 t ha−1 and 10 t ha−1 and the variety Vanessa F1 were associated with low percentages of deterioration. The best shelf-life was achieved with the variety Vanessa F1 fertilized with 5 t ha−1 of chicken manure, which showed the lowest deterioration (8.33% after 20 days of storage).